Restorative Justice dalam Perkara Tindak Pidana Pencurian (Studi Putusan Nomor 28/Pid.B/2022/Pn.Lbb) - Enny Yulistiawati; Arif Awangga (Syntax Literate, 2023)
Law in Indonesia is divided into criminal law and civil law. Criminal law is the law that regulates what actions are prohibited and gives punishment to those who violate them and regulates how to bring cases to court, for example theft. One of the law enforcement efforts in overcoming the crime of theft that is firm, consistent and integrated, can be done in one way, namely the application of restorative justice. The research method used is a normative juridical method with a law approach and a case approach. From the results of the study, it was found that the legal basis for restorative justice in the case of the crime of theft is based on the Supreme Court Regulation Number 02 of 2012 concerning Adjustment of the Limits of Minor Crimes and the Amount of Fines in the Criminal Code, Article 4 Memorandum of Understanding with the Chief Justice of the Supreme Court of the Republic of Indonesia Minister of Law and Human Rights Man, the Attorney General of the Republic of Indonesia, the Head of the Indonesian National Police regarding the Implementation of Adjustment on the Limits of Minor Crimes and the Amount of Fines, Quick Examination Procedures, and the Application of Restorative Justice Number: 131/KMA I SKB IX/2012 Number: M. HH - 07. HM. 03. 02 of 2012 Number: KEP - 06 /E IEJP /10/2012 Number: B/39/X/2012 Article 3 Regulation of the Indonesian National Police Number 8 of 2021 concerning Handling of Crimes Based on Restorative Justice and Article 4 paragraph (2 ), Article 5 paragraph (1) of the Prosecutor's Office Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. The judge's consideration in deciding restorative justice for the theft criminal case in the decision number 28/Pid.B/2022/Pn.Lbb was based on the testimony of witness Mulyono, several previous decisions related to restorative justice and Article 10 paragraph (1) of Law Number 48 Year 2009 on Judicial Power.